Matching in community-based organizations. - Arcand, J; Fafchamps, M (Elsevier, 2012)
Using a rich dataset from West Africa, we examine the household characteristics associated with membership in community-based organizations (CBOs). We find that on average it is the more fortunate members of rural society who belong in CBOs. In Senegal, the dominant criterion is land ownership. In Burkina Faso it is age and family ties with village authorities. Ethnicity plays a role as well: CBO membership is less likely for ethnic groups that traditionally emphasize livestock raising. Next we look for evidence of assortative matching along multiple dimensions, using an original methodology based on dyadic regressions. We find robust evidence of positive assorting by physical and ethnic proximity as well as by wealth and household size. Along certain dimensions, donor-sponsored CBOs are less elitist and more inclusive. But the reverse is true for other dimensions, particularly in Burkina Faso.